Blood coagulation in Prediabetes clusters-impact on all-cause mortality in individuals undergoing coronary angiography - Hörber, Sebastian; Prystupa, Katsiaryna; Jacoby, Johann; Fritsche, Andreas; Kleber, Marcus E.; Moissl-Blanke, Angela P.; Hellstern, Peter; Peter, Andreas; März, Winfried; Wagner, Róbert; Heni, Martin (Cardiovascular diabetology, 2024)
Metabolic clusters can stratify subgroups of individuals at risk for type 2 diabetes mellitus and related complications. Since obesity and insulin resistance are closely linked to alterations in hemostasis, we investigated the association between plasmatic coagulation and metabolic clusters including the impact on survival. Utilizing data from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study, we assigned 917 participants without diabetes to prediabetes clusters, using oGTT-derived glucose and insulin, high-density lipoprotein cholesterol, triglycerides, and anthropometric data. We performed a comprehensive analysis of plasmatic coagulation parameters and analyzed their associations with mortality using proportional hazards models. Mediation analysis was performed to assess the effect of coagulation factors on all-cause mortality in prediabetes clusters. Prediabetes clusters were assigned using published tools, and grouped into low-risk (clusters 1,2,4; n = 643) and high-risk (clusters 3,5,6; n = 274) clusters. Individuals in the high-risk clusters had a significantly increased risk of death (HR = 1.30; CI: 1.01 to 1.67) and showed significantly elevated levels of procoagulant factors (fibrinogen, FVII/VIII/IX), D-dimers, von-Willebrand factor, and PAI-1, compared to individuals in the low-risk clusters. In proportional hazards models adjusted for relevant confounders, elevated levels of fibrinogen, D-dimers, FVIII, and vWF were found to be associated with an increased risk of death. Multiple mediation analysis indicated that vWF significantly mediates the cluster-specific risk of death. High-risk prediabetes clusters are associated with prothrombotic changes in the coagulation system that likely contribute to the increased mortality in those individuals at cardiometabolic risk. The hypercoagulable state observed in the high-risk clusters indicates an increased risk for cardiovascular and thrombotic diseases that should be considered in future risk stratification and therapeutic strategies.
Gesehen am 25.02.2025